A polymer supported ascorbate functionalized task specific ionic liquid: an efficient reusable catalyst for 1, 3-dipolar cycloaddition. Issue 27 (24th February 2015) - Patil, Jayavant D.; Patil, Supriya A.; Pore, Dattaprasad M.
Abstract : In situ coalescence of copper on polymer supported ascorbate functionalized task specific ionic liquid, acts as an efficient catalyst for Huisgen 1, 3 dipolar cycloaddition. Abstract : A novel polymer supported ascorbate functionalized task specific ionic liquid was designed and synthesized. It has been demonstrated that the synthesized polymer supported ionic liquid acts as an efficient catalyst for regioselective Huisgen 1, 3-dipolar cycloaddition of aryldiazonium tetrafluoroborate, sodium azide and terminal alkyne, which provide a series of 1, 4-disubstituted-1, 2, 3-triazoles in high yields at room temperature as well as showing an aptitude for in situ incorporation of copper.